2014
DOI: 10.17116/jnevro2014114121112-122
|View full text |Cite
|
Sign up to set email alerts
|

The primary screening of patients with autonomic disorders in outpatient clinics in Russia (START1) using the Russian version of The Four-Dimensional Symptom Questionnaire (4DSQ)

Abstract: The linguistically validated Russian version of 4DSQ enabled to formalize the description of clinical profile of these patients. Cluster analysis of the results allowed to single out two superdomains by the pairwise combination somatization with distress (SDis) and anxiety with depression (ADep). The detection of superdomain SDis appears to be a population specific characteristic of autonomic nervous system disorders in the Russian Federation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A clearer explanation could be found should the factor analysis be carried out in a large-scale face-to-face investigation. Of note, many studies have confirmed the factor structure in different languages, including Polish, 27 Russian 28 and Turkish. 29 However, as we examined the Arabic version of 4DSQ, we concluded that three items need revision before it can effectively measure the underlying four constructs in Arabic-speaking populations.…”
Section: Discussionmentioning
confidence: 94%
“…A clearer explanation could be found should the factor analysis be carried out in a large-scale face-to-face investigation. Of note, many studies have confirmed the factor structure in different languages, including Polish, 27 Russian 28 and Turkish. 29 However, as we examined the Arabic version of 4DSQ, we concluded that three items need revision before it can effectively measure the underlying four constructs in Arabic-speaking populations.…”
Section: Discussionmentioning
confidence: 94%